GE_GERICHTE C/524/2015 vom 9. März 2016 - GE Cour de justice (2016)
DIMINUTION DE LOYER ; DROIT DE S'EXPLIQUER; RÉPLIQUE ; CONSTATATION DES FAITS ; HYPOTHÈQUE ; TAUX D'INTÉRÊT ; MÉTHODE RELATIVE ; MÉTHODE ABSOLUE | CO.270a.1; CPC.317.1